Analisis Miskonsepsi Siswa XI MIA 1 SMA Negeri 1 Pangkajene pada Materi Pokok Hidrokarbon - Reny, Reny; Astuti, Sry; Rahayu, Ayu (Indo-MathEdu Intellectuals Journal, 2023)
This descriptive research aims to analyze the student’s misconceptions on hydrocarbon subject that have been learned by STAD Type of Cooperative Learning Model. The subjects in research are 31 students of SMA Negeri 1 Pangkajene class XI MIA 1. The data was collected by 7 items essay test and intensified by interviews. The data was analyzed by descriptive statistic method to obtain percentage of the misconseption. The result of this research shows that student’s misconception is low category, 17% in determining C atom of primary, secondary, tertiary, and quaternary. In naming of alkanes, alkenes, and alkyne’s structure, is low category, average 24,5%. In understanding addition and subtitusi reaction of hydrocarbon is low category, 22,4%.  And low category, average 21,3% on misconception of hydrocarbon in generallydisciplining teachers and motivating them to comply with the foundation's policies is a problem that must be immediately found a solution. This research uses a qualitative approach, data sources obtained through interviews through zoom applications, documentation, and observation. This article found that PAUD al Ashriyyah Principal Nurul Iman in improving teacher discipline used autocratic style to be the dominant style, not seen other styles played by principals in the leadership model. The principal in improving the work discipline of his teachers does not always run smoothly, the obstacles and obstacles